基于RecurDyn的精密滚子链传动的运动特性仿真分析 - 侯红玲; 赵永强 (Jixie chuandong)
The roller chain is a kind of chain for transmitting mechanical power,and widely used in industrial and agricultural machinery.Taking 08 Btype short pitch precision roller chain as example,the most common ways of roller chain drive are analyzed,and the simulation analysis of motion characteristics of,the transmission efficiency and the dynamic load of the chain drive are carried out respectively.The results of simulation verify the basic characteristics of chain drive,the dynamic load size and transmission efficiency are predicted,the results are consistent with the theoretical analysis.The basis for the selection and application of chain drive in engineering is provided by this method,the basis for the design and type selection of other roller chain is also provided.